Survey of Relationship Between Health Promoting Lifestyle and Job Satisfaction in Male Nurses in Ahwaz City: A Descriptive Study - Nahid Hossein Abbasi; Maryam Agha Amiri (Iran University of Medical Sciences, 2022)
Background & Aims: Due to many professional concerns such as shift stress and job injuries in nursing, male nurses do not pay much attention to their health-promoting lifestyle. Due to the above factors, work-life quality decreases and leads to job dissatisfaction and related consequences such as stress, anxiety, and depression. This study aimed to determine the relationship between a health-promoting lifestyle and job satisfaction in male nurses. Materials & Methods: The present cross-sectional study was a descriptive correlational study. The study population included all male nurses in Ahwaz City working in educational and medical centers. Finally, 108 male nurses were enrolled in the study from May 2019 to September 2019 by the available sampling method. Data were collected through a questionnaire consisting of three parts: 1) Demographic characteristics, 2) Health-promoting Lifestyle Questionnaire, and 3) Minnesota Satisfaction Questionnaire. Data were analyzed using SPSS software v. 22. Results: The results of the study showed that most male nurses (55.6%) have a bachelor's degree (84.2%), have 1 to 5 years of work experience (68.5%), and are in the age group of 26-35 years (46/2%). The health-promoting lifestyle variable Mean±SD score was 162.16±23.4 at the excellent level, and the job satisfaction Mean±SD score was 56.43±7.98 at the moderate level. There was a significant relationship between some areas of lifestyle promoting health and job satisfaction. Conclusion: The health-promoting lifestyle score of male nurses in this study was good but not favorable in physical activity and stress management. Also, the average score of job satisfaction and areas of opportunities for advancement and leadership style were significant. Therefore, supporting nursing managers in implementing health habits such as facilitating and supporting healthy lifestyle choices and creating positive environmental changes leads to increased health-promoting lifestyles, job satisfaction, and reduced disability of male nurses.